Modified nano-powder as well as preparation method and application thereof

By forming an inorganic envelope layer and an acrylic (ester) polymer coating layer on the surface of the nano powder and covering the silicone resin layer, the shortcomings of existing sun protection products in waterproof and sweat-proof performance are solved, and a higher sun protection coefficient and better waterproof and sweat-proof effect are achieved.

CN119679635APending Publication Date: 2025-03-25GUANGZHOU KINGPOWDER TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411875603.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing sunscreen products have shortcomings in waterproof and sweat-proof performance, and the use of physical sunscreens is restricted by regulations, making it difficult to increase the sunscreen coefficient while maintaining the content unchanged.

Method used

The inorganic envelope agent and a monomer of acrylic (ester) polymer are reacted with the nanopowder to form an inorganic envelope layer and an acrylic (ester) polymer coating layer, and further coated with the silicone resin layer to improve the dispersion and adaptability of the nanopowder.

Benefits of technology

It improves the sun protection and waterproof and sweat-proof effect of nano powder, reduces the amount of film-forming agent, enhances the ultraviolet shielding ability of the product, and improves the adhesion of nano powder on the skin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119679635A_ABST
    Figure CN119679635A_ABST
Patent Text Reader

Abstract

The invention discloses modified nano powder as well as a preparation method and application thereof, and belongs to the technical field of cosmetics. The modified nano-powder is of a core-shell structure, takes nano-powder as a core, and comprises an inorganic hydrated oxide coating layer, an acrylic acid (ester) polymer coating layer and an organic silicon resin layer which are sequentially coated on the surface of the nano-powder. The preparation method provided by the invention not only simplifies the process of inorganic and organic dual surface treatment, but also ensures that each nanoparticle forms a uniform and compact dual organic coating layer with the same composition and structure. The modified nano-powder prepared by the invention has good dispersibility and adaptability, and can enhance the stability, sunscreen capability and waterproof and sweat-proof effects of products when being applied to cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cosmetics, and in particular to a modified nano powder and a preparation method and application thereof. Background Art

[0002] For sunscreen products, users still generally focus on the sunscreen effect, and also care about its waterproof and sweat-proof properties. However, most sunscreen products currently on the market have the following shortcomings: First, the ability to be waterproof and sweat-proof is weak, and sunscreen products need to be reapplied within a short period of time outdoors. Second, in order to achieve high sunscreen ability, too much physical sunscreen nano titanium dioxide or nano zinc oxide is added to the formula, increasing product costs; secondly, too much chemical sunscreen is added to the formula, which irritates the skin and is difficult to meet consumers' demand for product safety. Moreover, the current cosmetics regulations allow the use of zinc oxide and titanium dioxide as physical sunscreens in cosmetics, and there are restrictions on the amount of physical sunscreens added to sunscreens or personal care compositions. On the premise of keeping the content of physical sunscreens unchanged, further improving its sun protection factor has become a technical point.

[0003] Many technical solutions have emerged at home and abroad to directly treat the surface of physical sunscreen nanopowders or to compound them with other substances to increase the added value of nanopowders. In terms of surface treatment and modification of nanopowders, most technical solutions are still at the level of using coupling agents to treat the surface of nanopowders to improve their dispersion performance, which is difficult to comprehensively improve the sunscreen effect and waterproof and sweat-proof performance of physical sunscreens themselves; for the technical level of combining or compounding nanopowders with other substances, there are limitations in the application system, and the compatibility of the combined substances and the formula components must be considered when designing the formula.

[0004] At present, there are many patents for surface modification of powders at home and abroad. In patent US005238678A, the inventors coated aluminum powder with a copolymer having an acrylate monomer structure for the first layer and a polymerized carboxylic acid for the second layer to improve the water resistance, oil resistance, softness and adhesion to the skin of the sample, but the acrylic acid and carboxylic acid groups may be exposed, and the acrylic acid copolymer chain is anionic, which limits the application range of the powder. Patent CN110339072A provides a waterproof and sweat-resistant composition, which simultaneously embeds sunscreen, sunscreen powder and styrene / acrylic acid (ester) copolymer sodium with a hollow sphere structure encapsulated by tara gum through a highly branched structure of trimethylsiloxysilicate / polymethylsilsesquioxane to form a double-layer three-dimensional film, which improves the ultraviolet protection effect of the applied product, but the sunscreen is embedded only through the branched structure of the macromolecule to form a steric hindrance. In subsequent experimental applications, the sunscreen is easily separated and dispersed in the system under the action of high-speed shear, and a complete film cannot be formed on the surface of the sunscreen powder. Patent CN107072893 A provides a composition comprising a plurality of multi-layer spherical composite particles and a UV shielding agent, which is applied to products to enhance the resistance of skin and hair to ultraviolet rays. The composite particles are specifically SiO2 / TiO2 / SiO2, and the titanium dioxide is only surface coated with an inorganic coating agent without any organic surface treatment, so its dispersibility in the system is limited. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a modified nano powder and a preparation method and application thereof, wherein an inorganic coating agent and monomers of acrylic (ester) polymers are reacted with nano powders in the same system to form an inorganic coating layer while the monomers of acrylic (ester) polymers undergo in-situ polymerization and film-forming coating reactions, and then further coated with an organic silicone resin layer, thereby simplifying the process of surface treatment of nano powders with inorganic coating agents and dual organic modifiers, improving the uniformity and density of the nano powder surface coating layer, improving the dispersibility and adaptability of nano particles in product applications, and enhancing the sun protection ability and waterproof and sweat-proof effects of the applied products.

[0006] The first object of the present invention is to provide a modified nano powder, wherein the modified nano powder is a core-shell structure, with the nano powder as the core, and an inorganic hydrated oxide coating layer, an acrylic (ester) polymer coating layer and an organic silicone resin layer sequentially wrapped on the surface of the nano powder;

[0007] The hydroxyl groups in the inorganic hydrated oxide coating layer are connected to the carboxyl groups in the acrylic acid (ester) polymer monomers through chemical bonding;

[0008] In-situ polymerization of acrylic acid (ester) polymer monomers on the surface of the inorganic hydrated oxide coating layer forms an acrylic acid (ester) polymer coating layer;

[0009] The hydroxyl group at the terminal group of the organic silicone resin is chemically bonded with the carboxyl group in the acrylic (ester) polymer to form the organic silicone resin layer.

[0010] In some embodiments of the present invention, the powder includes titanium dioxide and zinc oxide;

[0011] The particle size of the nano powder is 10-100 nm.

[0012] In some embodiments of the present invention, the inorganic hydrated oxide coating layer includes aluminum hydroxide and / or silicon dioxide.

[0013] In some embodiments of the present invention, the acrylic acid (ester) polymer includes a polymer having an unsaturated acrylic acid group.

[0014] The second object of the present invention is to provide a method for preparing a modified nanopowder, comprising the following steps:

[0015] Providing a slurry containing nano powder particles, and adjusting the slurry to be alkaline;

[0016] Adding an inorganic coating agent to the alkaline slurry and mixing, then adding an acrylic acid (ester) polymer monomer and mixing and reacting to obtain powder A;

[0017] Adding a silicone resin dispersion to the powder A and stirring evenly to obtain a powder B;

[0018] The powder B is subjected to solid-liquid separation to obtain a solid phase, and the solid phase is the modified nanopowder.

[0019] In some embodiments of the present invention, the pH value of the alkaline slurry is 9 to 10;

[0020] The inorganic coating agent is selected from water-soluble aluminum salts and / or water-soluble silicon salts;

[0021] The amount of the inorganic coating agent is 5-20wt% of the nano powder particles.

[0022] In some embodiments of the present invention, the amount of the acrylic (ester) polymer monomer is 1-15wt% of the nano powder particles;

[0023] The monomers of the acrylic acid (ester) polymer include one or more of acrylic acid, methacrylic acid, octyl acrylic acid, ethylhexyl acrylate, methyl acrylate, lauryl methacrylate, ethyl acrylic acid, and propyl acrylic acid.

[0024] In some embodiments of the present invention, the silicone resin includes one or more of trimethylsiloxysilicate, polymethylsilsesquioxane, trimethylsiloxysilicate / dimethiconol crosspolymer, diphenylsiloxyphenyl trimethicone, polypropylsilsesquioxane, and polyphenylsilsesquioxane;

[0025] The amount of the organic silicon resin used is 1-10 wt% of the nano powder particles.

[0026] The third object of the present invention is to provide a cosmetic comprising the modified nano powder.

[0027] In some embodiments of the present invention, the cosmetics include sunscreen cream, liquid foundation, BB cream, CC cream, loose powder, primer or isolation cream.

[0028] The above technical solution of the present invention has the following advantages compared with the prior art:

[0029] (1) The present invention uses film-forming acrylic (ester) polymers and silicone resins to directly form stable chemical bonds with the surface of physical sunscreen nanopowders, thereby constructing a friction-resistant and migration-resistant sunscreen film from both molecular and particle dimensions. While maintaining the content of the physical sunscreen, the ultraviolet shielding ability of the product is further improved, and the amount of film-forming agent added in the sunscreen product formula can be reduced, giving the product excellent waterproof and sweat-proof effects.

[0030] (2) The present invention uses acrylic (ester) polymers and silicone resins to perform dual surface treatment on nanopowders, wherein the coating of the acrylic (ester) polymer layer is directly in the same system of inorganic coating treatment in the form of monomers to undergo in-situ polymerization reaction and simultaneously form a polymer coating on the surface of the nanopowder, thereby simplifying the process of modifying the nanopowder with inorganic coating agents and dual organic surface treatment agents; the polymerization reaction and surface bonding reaction of the reactive acrylic (ester) polymer monomers on the surface of the nanopowder are carried out simultaneously to ensure that a dense coating layer with uniform composition and structure is formed on the surface of the nanopowder, thereby reducing the difference in surface modification ratio between single nanopowder particles.

[0031] (3) The present invention forms a double film-forming agent coating layer on the surface of the nanopowder. The macromolecular chain of the film-forming agent forms a steric hindrance on the surface of the nanopowder, greatly reducing the probability of soft agglomeration of the nanoparticles due to high surface energy, thereby improving the anti-flocculation property of the nanoparticles when used in products. The use of an organic silicone resin with a silicon-oxygen bonding structure as the outermost layer improves the compatibility of the nanoparticles with the formulation components, thereby improving the adaptability of the nanopowder in product applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0033] Figure 1 It is the ultraviolet light transmittance curve diagram of the nano powder dispersion slurry of Example 9 of the present invention and Comparative Example 2.

[0034] Figure 2 These are the hydrophobic angle test graphs of the nanopowders prepared in Example 9 and Comparative Example 2. In the graph, A represents the hydrophobic angle test graph of the modified nanopowder prepared in Example 9, and B represents the hydrophobic angle test graph of the nanopowder prepared in Comparative Example 2.

[0035] Figure 3 These are microscopic observation pictures of the pure physical sunscreen product bodies of Application Example 1 and Application Comparative Example 1. In the pictures, A represents the microscopic observation picture of the pure physical sunscreen product body of Application Example 1, and B represents the microscopic observation picture of the pure physical sunscreen product body of Application Comparative Example 1. DETAILED DESCRIPTION

[0036] In order to solve the technical problems pointed out in the background technology, the present invention achieves the purpose of the present invention by the following methods:

[0037] The present invention provides a modified nano powder, wherein the modified nano powder is a core-shell structure, with the nano powder as the core, and an inorganic hydrated oxide coating layer, an acrylic (ester) polymer coating layer and an organic silicon resin layer sequentially wrapped on the surface of the nano powder;

[0038] The hydroxyl groups in the inorganic hydrated oxide coating layer are connected to the carboxyl groups in the acrylic acid (ester) polymer monomers through chemical bonding;

[0039] In-situ polymerization of acrylic acid (ester) polymer monomers on the surface of the inorganic hydrated oxide coating layer forms an acrylic acid (ester) polymer coating layer;

[0040] The hydroxyl group at the terminal group of the organic silicone resin is chemically bonded with the carboxyl group in the acrylic (ester) polymer to form the organic silicone resin layer.

[0041] In a specific embodiment of the present invention, the powder includes titanium dioxide and / or zinc oxide;

[0042] The particle size of the nanopowder is 10-100nm, preferably 15-80nm. If the particle size of the nanopowder of the present invention is too small, it is easy to agglomerate during the processing process, which is not conducive to dispersion and has a great impact on the stability of the applied product; if the particle size of the nanoparticle is too large, the sunscreen product will appear white when used, and the experience is poor.

[0043] In a specific embodiment of the present invention, the inorganic hydrated oxide coating layer includes aluminum hydroxide and / or silicon dioxide.

[0044] In a specific embodiment of the present invention, the acrylic acid (ester) polymer includes a polymer having an unsaturated acrylic acid group.

[0045] The present invention also provides a method for preparing a modified nano powder, comprising the following steps:

[0046] Providing a slurry containing nano powder particles, and adjusting the slurry to be alkaline;

[0047] Add an inorganic coating agent to the alkaline slurry and mix, then add a monomer of an acrylic acid (ester) polymer and mix and react for 1 to 10 hours (preferably 3 to 8 hours) to obtain powder A;

[0048] Adding the organic silicone resin dispersion to the powder A and stirring for 2-8 hours to obtain powder B;

[0049] The powder B is subjected to solid-liquid separation to obtain a solid phase, and the solid phase is the modified nanopowder.

[0050] Furthermore, the solvent of the slurry containing nano-powder particles is water.

[0051] In the process of preparing the slurry, the apparatus used is not specifically limited, and the nano powder particles can be dispersed evenly. The preparation of the nano powder slurry here is a wet process operation when the nano powder is inorganically coated. The reaction in the water medium can better disperse the treatment agent evenly, fully contact with the nano powder particles, and coat more evenly and firmly, and the polymerization reaction of the monomer of the acrylic (ester) polymer is also more continuous and complete.

[0052] In a specific embodiment of the present invention, the pH value of the alkaline slurry is 9-10; the main purpose of adjusting the pH of the present invention is to prepare an inorganic hydrated oxide coating layer by a chemical precipitation method, and the soluble salt is hydrolyzed by adjusting the pH to deposit on the surface of the nano powder particles in the form of a skin, forming a complete, thin and dense hydrated oxide inorganic coating. The present invention coats the surface of the nano powder with a layer of inorganic oxide protective film to establish a barrier between the nano powder and the surrounding medium, thereby reducing the surface energy and photocatalytic activity of the nano powder, which is beneficial to improving its light resistance and weather resistance.

[0053] The inorganic coating agent is selected from water-soluble aluminum salts and / or water-soluble silicon salts; further, the water-soluble aluminum salts include one or more of aluminum sulfate, sodium aluminate, aluminum nitrate, aluminum chloride, aluminum fluoride, aluminum phosphate, aluminum oxalate, and aluminum citrate; the water-soluble silicon salts include one or more of sodium silicate, silicon acetate, lithium silicate, potassium silicate, magnesium silicate, calcium silicate, and ammonium silicate.

[0054] The amount of the inorganic coating agent is 5-20wt% of the nanopowder particles; illustratively, it can be 5Wt%, 6Wt%, 7Wt%, 8Wt%, 9Wt%, 10Wt%, 11Wt%, 12Wt%, 13Wt%, 14Wt%, 15Wt%, 16Wt%, 17Wt%, 18Wt%, 19Wt%, 20Wt%, etc., or any interval value between any two values.

[0055] In a specific embodiment of the present invention, the amount of the monomer of the acrylic acid (ester) polymer is 1-15Wt% of the nano powder particles, for example, it can be 1Wt%, 2Wt%, 3Wt%, 4Wt%, 5Wt%, 6Wt%, 7Wt%, 8Wt%, 9Wt%, 10Wt%, 11Wt%, 12Wt%, 13Wt%, 14Wt%, 15Wt%, etc., or any interval value between any two values;

[0056] The monomers of the acrylic acid (ester) polymer include one or more of octyl acrylic acid, acrylic acid, methacrylic acid, ethylhexyl acrylate, methyl acrylate, lauryl methacrylate, ethyl acrylic acid, and propyl acrylic acid.

[0057] In the present invention, an inorganic coating agent and a monomer of an acrylic (ester) polymer are respectively added dropwise to a nano-powder dispersion slurry, so that the reaction is carried out in the same system, simplifying the process of inorganic and organic composite surface treatment; and after the inorganic coating agent is added first, the surface of the nano-powder is chemically bonded with an inorganic hydrated oxide, and more surface hydroxyl groups brought by the inorganic coating can be further used as anchoring points for acrylic monomers to carry out in-situ polymerization reaction and film coating, thereby ensuring that the proportions of surface modifiers of different nano-powder particles are equivalent, forming a uniform and dense organic polymer coating layer, and finally preparing a nano-powder with a narrow particle size distribution and regular particle shape.

[0058] Furthermore, by directly dropping the monomer of acrylic (ester) polymer, the inherent free radicals on the surface of the nano powder particles can automatically excite the surface active points without adding additional initiators, directly triggering the active monomers to perform in-situ chemical reactions, and directly performing polymerization reactions on the surface of the nano powder. As the polymerization continues, the coating finally grows to form a continuous acrylic (ester) polymer with film-forming properties; at the same time, the carboxyl groups on each monomer also chemically bond with the hydroxyl groups on the surface of the inorganically coated nano powder, and the nano powder is coated with an organic polymer. That is, the polymerization reaction and surface bonding reaction of the monomer of acrylic (ester) polymer on the surface of the nano powder are carried out simultaneously, and the formed macromolecular chains are directly surrounded and coated on the powder surface, so that the polymer and the nano powder form a stable binding force under the dual mechanism of chemical bonding and physical action, and the formed acrylic (ester) polymer is prevented from exposing too many external branches, and the anionicity on the molecular chain is prevented from limiting its application range.

[0059] In a specific embodiment of the present invention, the silicone resin includes one or more of trimethylsiloxysilicate, polymethylsilsesquioxane, trimethylsiloxysilicate / polydimethylsiloxane crosspolymer, diphenylsiloxyphenyl polytrimethylsiloxane, polypropylsilsesquioxane, and polyphenylsilsesquioxane;

[0060] The amount of the silicone resin used is 1-10Wt% of the nanopowder particles. For example, it can be 1Wt%, 2Wt%, 3Wt%, 4Wt%, 5Wt%, 6Wt%, 7Wt%, 8Wt%, 9Wt%, 10Wt%, etc., or any interval value between any two values.

[0061] In a specific embodiment of the present invention, the dispersion medium of the organic silicone resin dispersion is a volatile liquid, and is not limited to a specific type, as long as it can disperse and open the organic silicone resin structure.

[0062] Furthermore, powder A is directly added to the silicone resin dispersion, and the molecular chains of the polymer are opened after dispersion to form a certain steric hindrance. The viscosity of the dispersion also limits the soft agglomeration of the nanopowder particles in the slurry due to van der Waals forces, so that the nanopowder is evenly dispersed, the contact area with the silicone resin is increased, and it is easy to react.

[0063] In the present invention, the silicone resin is an organic polymer with Si-O-Si as the main chain, organic groups connected to silicon atoms, and hydroxyl groups at the end groups; the hydroxyl groups can be chemically bonded with the carboxyl groups in the acrylic (ester) polymer on the surface of the powder A described in step S1, thereby neutralizing the excessive carboxyl groups on the surface of the powder A; at the same time, the macromolecular chain is cross-linked and entangled with the formed acrylic (ester) polymer molecular chain, and the silanol structures on the chain are mutually associated and aggregated to form a continuous three-dimensional network structure film covering the surface of the nanopowder, further avoiding the exposure of anions of the acrylic (ester) polymer molecular chain to affect the stability of the sunscreen product; the silicone resin surface treatment of nanopowder can also improve the compatibility of the powder in silicone oil system products; as the outermost layer, the exposed hydroxyl groups can form hydrogen bonds with the surface of human skin, which is beneficial for the spreading of the nanopowder on the skin, so that the nanopowder has better adhesion on the surface of human skin, thereby improving the waterproof, sweat-proof and migration resistance of the sunscreen product.

[0064] In a specific embodiment of the present invention, the solid phase is further dried and crushed. The drying and crushing are conventional technical means in the art, and the instruments used are not specifically limited.

[0065] The third object of the present invention is to provide a cosmetic comprising the modified nano powder.

[0066] In some embodiments of the present invention, the cosmetics include sunscreen cream, liquid foundation, BB cream, CC cream, loose powder, primer cream, and isolation cream.

[0067] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0068] Example 1

[0069] This embodiment provides a method for preparing modified nanopowders, and the specific steps are as follows:

[0070] S1. Add 100 g of 15 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 9 g of water-soluble aluminum sulfate, stir evenly, then drop 3 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0071] S2. Powder A is transferred into a stirrer, 1 g of trimethylsiloxysilicate isomeric dodecane solution is added, and the mixture is stirred for 4 hours to obtain powder B;

[0072] S3. Powder B is filtered through a filter, dried in an oven at 100° C., and then crushed in a grinder to obtain modified nano powder.

[0073] Example 2

[0074] This embodiment provides a method for preparing modified nanopowders, and the specific steps are as follows:

[0075] S1. Add 100 g of 30 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 9 g of water-soluble aluminum sulfate, stir evenly, then drop 3 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0076] S2. Powder A is transferred into a stirrer, 1 g of trimethylsiloxysilicate isomeric dodecane solution is added, and the mixture is stirred for 4 hours to obtain powder B;

[0077] S3. Powder B is filtered through a filter, dried in an oven at 100° C., and then crushed in a grinder to obtain modified nano powder.

[0078] Example 3

[0079] This embodiment provides a method for preparing modified nanopowders, and the specific steps are as follows:

[0080] S1. Add 100 g of 45 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 9 g of water-soluble aluminum sulfate, stir evenly, then drop 3 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0081] S2. Powder A is transferred into a stirrer, 1 g of trimethylsiloxysilicate isomeric dodecane solution is added, and the mixture is stirred for 4 hours to obtain powder B;

[0082] S3. Powder B is filtered through a filter, dried in an oven at 100° C., and then crushed in a grinder to obtain modified nano powder.

[0083] Example 4

[0084] This embodiment provides a method for preparing modified nanopowders, and the specific steps are as follows:

[0085] S1. Add 100 g of 60 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 9 g of water-soluble aluminum sulfate, stir evenly, then drop 3 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0086] S2. Powder A is transferred into a stirrer, 1 g of trimethylsiloxysilicate isomeric dodecane solution is added, and the mixture is stirred for 4 hours to obtain powder B;

[0087] S3. Powder B is transferred into a filter for filtering, then transferred into an oven at 100° C. for drying, and then transferred into a grinder for crushing to obtain modified nano powder.

[0088] Example 5

[0089] This embodiment provides a method for preparing modified nanopowders, and the specific steps are as follows:

[0090] S1. Add 100 g of 15 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 12 g of water-soluble aluminum sulfate, stir evenly, then drop 3 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0091] S2. Powder A is transferred into a stirrer, 1 g of trimethylsiloxysilicate isomeric dodecane solution is added, and the mixture is stirred for 4 hours to obtain powder B;

[0092] S3. Powder B is transferred into a filter for filtering, then transferred into an oven at 100° C. for drying, and then transferred into a grinder for crushing to obtain modified nano powder.

[0093] Example 6

[0094] This embodiment provides a method for preparing modified nanopowders, and the specific steps are as follows:

[0095] S1. Add 100 g of 15 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 15 g of water-soluble aluminum sulfate, stir evenly, then drop 3 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0096] S2. Powder A is transferred into a stirrer, 1 g of trimethylsiloxysilicate isomeric dodecane solution is added, and the mixture is stirred for 4 hours to obtain powder B;

[0097] S3. Powder B is transferred into a filter for filtering, then transferred into an oven at 100° C. for drying, and then transferred into a grinder for crushing to obtain modified nano powder.

[0098] Example 7

[0099] This embodiment provides a method for preparing modified nanopowders, and the specific steps are as follows:

[0100] S1. Add 100 g of 15 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 12 g of water-soluble aluminum sulfate, stir evenly, then drop 6 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0101] S2. Powder A is transferred into a stirrer, 1 g of trimethylsiloxysilicate isomeric dodecane solution is added, and the mixture is stirred for 4 hours to obtain powder B;

[0102] S3. Powder B is transferred into a filter for filtering, then transferred into an oven at 100° C. for drying, and then transferred into a grinder for crushing to obtain modified nano powder.

[0103] Example 8

[0104] This embodiment provides a method for preparing modified nanopowders, and the specific steps are as follows:

[0105] S1. Add 100 g of 15 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 12 g of water-soluble aluminum sulfate, stir evenly, then drop 9 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0106] S2. Powder A is transferred into a stirrer, 1 g of trimethylsiloxysilicate isomeric dodecane solution is added, and the mixture is stirred for 4 hours to obtain powder B;

[0107] S3. Powder B is transferred into a filter for filtering, then transferred into an oven at 100° C. for drying, and then transferred into a grinder for crushing to obtain modified nano powder.

[0108] Example 9

[0109] This embodiment provides a method for preparing modified nanopowders, and the specific steps are as follows:

[0110] S1. Add 100 g of 15 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 12 g of water-soluble aluminum sulfate, stir evenly, then drop 6 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0111] S2, transfer powder A into a stirrer, add 3 g of isomeric dodecane solution of trimethylsiloxysilicate, and stir thoroughly for 4 hours to obtain powder B;

[0112] S3. Powder B is transferred into a filter for filtering, then transferred into an oven at 100° C. for drying, and then transferred into a grinder for crushing to obtain modified nano powder.

[0113] Example 10

[0114] This embodiment provides a method for preparing modified nanopowders, and the specific steps are as follows:

[0115] S1. Add 100 g of 15 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 12 g of water-soluble aluminum sulfate, stir evenly, then drop 6 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0116] S2. Powder A is transferred into a stirrer, 5 g of isomeric dodecane solution of trimethylsiloxysilicate is added, and the mixture is stirred for 4 hours to obtain powder B;

[0117] S3. Powder B is filtered through a filter, dried in an oven at 100° C., and then crushed in a grinder to obtain modified nano powder.

[0118] Embodiment 11

[0119] This embodiment provides a method for preparing modified nanopowders, and the specific steps are as follows:

[0120] S1. Add 100 g of 50 nm zinc oxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 12 g of water-soluble aluminum sulfate, stir evenly, then drop 6 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0121] S2, transfer powder A into a stirrer, add 3 g of isomeric dodecane solution of trimethylsiloxysilicate, and stir thoroughly for 4 hours to obtain powder B;

[0122] S3. Powder B is filtered through a filter, dried in an oven at 100° C., and then crushed in a grinder to obtain modified nano powder.

[0123] Comparative Example 1

[0124] This comparative example provides a nano powder, which is different from Examples 1-4 in that the original particle size of the processed nano powder particles is different. The specific steps are as follows:

[0125] S1. Add 100 g of 5 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 9 g of water-soluble aluminum sulfate, stir evenly, then drop 3 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0126] S2. Powder A is transferred into a stirrer, 1 g of trimethylsiloxysilicate isomeric dodecane solution is added, and the mixture is stirred for 4 hours to obtain powder B;

[0127] S3. Powder B is filtered through a filter, dried in an oven at 100°C, and crushed in a grinder to obtain nano powder.

[0128] Comparative Example 2

[0129] This comparative example provides a nano powder, which is different from Example 9 in that only inorganic coating treatment is performed on the nano powder, and no organic polymer coating treatment is performed. The specific steps are as follows:

[0130] S1. Add 100 g of 15 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, add 12 g of water-soluble aluminum sulfate dropwise, stir well for 6 hours, and react to obtain powder A;

[0131] S2. Powder A is filtered through a filter, dried in an oven at 100° C., and then crushed in a grinder to obtain coated nanopowder.

[0132] Comparative Example 3

[0133] This comparative example provides a nano powder, which is different from Example 9 in that only inorganic coating and acrylic (ester) polymer single-layer organic coating treatment are performed on the nano powder, and no silicone resin coating treatment is performed. The specific steps are as follows:

[0134] S1. Add 100 g of 15 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, drop 12 g of water-soluble aluminum sulfate, stir evenly, then drop 6 g of octyl acrylic acid, stir well for 6 hours, and react to obtain powder A;

[0135] S2. Powder A is filtered through a filter, dried in an oven at 100°C, and crushed in a grinder to obtain nano powder.

[0136] Comparative Example 4

[0137] This comparative example provides a nano powder, which is different from Example 9 in that only inorganic coating and single-layer organic coating of silicone resin are performed on the nano powder, and acrylic acid (ester) polymer coating is not performed. The specific steps are as follows:

[0138] S1. Add 100 g of 15 nm titanium dioxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, add 12 g of water-soluble aluminum sulfate dropwise, stir well for 6 hours, and react to obtain powder A;

[0139] S2, transfer powder A into a stirrer, add 3 g of isomeric dodecane solution of trimethylsiloxysilicate, and stir thoroughly for 4 hours to obtain powder B;

[0140] S3. Powder B is filtered through a filter, dried in an oven at 100°C, and then crushed in a grinder to obtain nano powder.

[0141] Comparative Example 5

[0142] This comparative example provides a nano powder, which is different from Example 11 in that only inorganic coating treatment is performed on the nano powder, and no organic polymer coating treatment is performed. The specific steps are as follows:

[0143] S1. Add 100 g of 50 nm zinc oxide and deionized water into a stirrer, stir evenly, adjust the pH to 10 with a 10 wt % sodium hydroxide aqueous solution, dropwise add 12 g of water-soluble aluminum sulfate, stir well for 6 hours, and react to obtain powder A;

[0144] S2. Powder A is filtered through a filter, dried in an oven at 100°C, and then crushed in a grinder to obtain coated nanopowder.

[0145] Sunscreen performance test

[0146] The nano powder and the oil C12-15 alcohol benzoate were mixed evenly, and dispersed by a high-speed homogenizer to prepare a dispersion slurry with a powder content of 10%. The dispersion slurry was tested for sunscreen performance using a Labsphere UV-2000S ultraviolet transmittance analyzer according to the specific test steps for in vitro sunscreen performance in the relevant regulations ISO24443.

[0147] Table 1 Dispersion slurry sunscreen performance test results

[0148] SPF value UVAPF value Example 1 26.27 9.08 Example 2 23.09 8.82 Example 3 20.65 7.28 Example 4 19.95 7.64 Example 5 30.98 11.69 Example 6 30.89 11.97 Example 7 33.42 12.84 Example 8 34.52 12.96 Example 9 37.40 14.14 Example 10 38.89 15.56 Embodiment 11 9.38 6.97 Comparative Example 1 22.61 7.01 Comparative Example 2 21.62 6.15 Comparative Example 3 24.08 8.02 Comparative Example 4 25.01 8.62 Comparative Example 5 3.20 2.73

[0149] From Table 1 and Appendix Figure 1 The results show that:

[0150] From Examples 1-11, Comparative Examples 1-5 and Figure 1 From the data of Example 9 and Comparative Examples 3-4, it can be seen that after the nanopowder is subjected to double organic treatment, its SPF value and UVAPF value are both improved, indicating that the nanopowder can be treated with film-forming acrylic (ester) polymers and silicone resins to improve the sunscreen effect of the nanopowder itself. When applied to products, the sun protection factor of the product can be further improved while keeping the content of physical sunscreen unchanged. It can be seen from the data of Example 9 and Comparative Examples 3-4 that the double surface treatment of the powder has a better sunscreen effect than the single layer treatment. It can be seen that after the double treatment, the macromolecules on the powder surface form a larger steric hindrance, making it more completely dispersed and forming a more uniform sunscreen film.

[0151] Objectively, the original particle size of the nanopowder has a certain influence on the sunscreen effect of the nanopowder itself; from the data of Examples 1-4 and Comparative Example 1, it can be seen that the smaller the original particle size, the better the sunscreen effect; however, the nanopowder with a smaller particle size in Comparative Example 1 was treated and still did not have a higher sun protection index than that of Example 1, indicating that when the particle size of the nanopowder is too small, its surface energy is larger and it is easier to agglomerate, which affects the organic coating treatment and the agglomerated nanopowder cannot completely maintain its own properties.

[0152] From the comparison between Example 1 and Examples 5-6, with the increase of the inorganic coating agent, the SPF value and the UVAPF value show a trend from increasing to flattening. It can be seen that when the inorganic coating agent reaches a certain amount, it can reach saturation coating on the surface of the nanopowder, reducing the photocatalytic activity of the nanopowder, improving the stability and anti-ultraviolet ability, and highlighting its excellent special properties. In the above embodiment, when the amount of the inorganic coating agent is 12wt% of the nanopowder, it is the above optimal ratio.

[0153] From the comparison between Example 5 and Examples 7-8, with the increase of the monomer of the acrylic (ester) polymer, the SPF value and UVAPF value show a trend from increasing to flattening, indicating that as the amount of monomer increases, more polymers are formed on the powder surface, the coating layer is more complete, the film-forming property of the nano powder itself is stronger, and its sunscreen effect is enhanced; when too much is used, the excess monomers are self-associated and attached to the powder surface, and will still be desorbed under strong stirring or extrusion during subsequent processing. Therefore, in order to reduce production costs, the optimal amount of the monomer of the acrylic (ester) polymer is 6wt% of the nano powder.

[0154] 5. From the data results of Examples 7 and 9-10, it can be seen that the sunscreen ability of the powder increases with the increase in the amount of silicone resin used. When the amount is a certain, the value does not change significantly. The silicone resin coating of the nanopowder not only improves its film-forming property but also improves the spreading ability of the nanopowder, achieving single particle dispersion and forming a uniform sunscreen film layer, thereby improving the sunscreen effect. However, too much silicone resin is not chemically bonded to the nanopowder and is easily filtered out in the filtering step. Therefore, the optimal amount of silicone resin is 3wt% of the nanopowder.

[0155] Contact angle test

[0156] Wettability is an important parameter when powder and liquid are mixed, and is mainly measured by contact angle.

[0157] The measurement was performed using an SDC-350 contact angle meter. An appropriate amount of nanopowder was taken and pressed into a cake using a mold. Deionized water and artificial sweat were used as contact liquids, respectively, and the measurement was performed according to the operating steps of the meter. The larger the contact angle, the stronger the powder's ability to resist water and sweat, that is, the liquid is not easy to wet the powder. The contact angle test results of different contact liquids are shown in Table 2.

[0158] Table 2 Contact angle test results of different contact liquids

[0159] Deionized water Artificial sweat Example 1 104.028° 101.325° Example 2 105.162° 102.425° Example 3 104.206° 102.063° Example 4 105.786° 102.542° Example 5 111.985° 106.896° Example 6 112.896° 105.756° Example 7 118.925° 114.469° Example 8 119.381° 114.923° Example 9 122.874° 120.201° Example 10 122.520° 121.358° Embodiment 11 123.792° 119.988° Comparative Example 1 101.920° 98.018° Comparative Example 2 0.615° 0.447° Comparative Example 3 91.934° 90.802° Comparative Example 4 89.286° 87.637° Comparative Example 5 0.412° 0.574°

[0160] From Table 2 and Appendix Figure 2 The results show that:

[0161] 1. From Examples 1-11, Comparative Examples 2-5 and the accompanying Figure 2 The results show that the contact angles of Comparative Examples 2 and 5 are both close to 0°, indicating that the nanopowder is not easily wetted by liquid after the organic coating treatment, which improves the waterproof and sweat-proof effect of the powder. Comparative Example 9 and Comparative Examples 3-4 show that the double surface treatment using acrylic acid (ester) polymer and silicone resin makes up for the deficiency of a single coating agent and synergistically improves the waterproof and sweat-proof effect.

[0162] 2. From the comparison results of Examples 1-4 and Comparative Example 1, it can be seen that the original particle size of the nanopowder particles has a certain influence on the surface-treated nanopowder. When the particle size of the nanopowder is too small, during the wet process, it is easy to spontaneously aggregate due to the strong van der Waals force between the nanopowder particles, which in turn affects the coating effect of the inorganic coating and the organic polymer, and ultimately leads to differences in waterproof and sweat-proof capabilities.

[0163] 3. From the comparison results of Example 1 and Examples 5-6, it can be seen that as the amount of inorganic coating agent increases, the contact angle gradually increases. When it reaches a certain amount, the increase in the contact angle is not obvious, indicating that the inorganic coating agent forms a dense inorganic coating layer on the surface of the nanopowder and has provided sufficient anchoring points for the polymerization reaction of the monomer of the acrylic acid (ester) polymer. Therefore, when the amount of the inorganic coating agent is 12Wt% of the nanopowder, it is the above-mentioned optimal ratio.

[0164] 4. From the comparison results of Example 5 and Examples 7-8, it can be seen that the contact angle increases with the increase in the amount of the acrylic (ester) polymer monomer. When a certain amount is reached, the contact angle increases slowly, indicating that the acrylic (ester) polymer monomer has completed the in-situ polymerization reaction and formed a saturated film-forming coating layer on the surface of the nanopowder. The addition of too much monomer may only cause the excess monomer to make a core coating reaction. The spontaneous bonding between the monomers is attached to the surface of the nanopowder through physical action, rather than directly chemically bonding with the nanopowder. In order to reduce the production cost of the organic surface coating of the nanopowder, the optimal amount of the acrylic (ester) polymer monomer is 6wt% of the nanopowder.

[0165] 5. From the comparison results of Example 7 and Examples 9-10, it can be seen that as the amount of the silicone resin film-forming agent increases, the contact angle increases rapidly. However, when a certain amount is reached, the contact angle does not increase significantly, indicating that the hydroxyl groups exposed on the surface of the nanopowder and the carboxyl groups of the acrylic (ester) polymer have been completely chemically bonded with the hydroxyl groups on the silicone resin chain. Adding too much silicone resin may cause excessive overflow problems. The optimal amount of silicone resin is 3Wt% of the nanopowder.

[0166] Application Example 1

[0167] The modified nano powders prepared in Examples 9 and 11 of the present invention were formulated according to the pure physical sunscreen product formula shown in Table 3 to obtain sample A. The total mass of the formula components was 100 g.

[0168] Application Comparative Example 1

[0169] 1. The nanopowders prepared in Comparative Examples 2 and 5 of the present invention were formulated according to the pure physical sunscreen product formula shown in Table 3 to obtain sample B. The total mass of the formula components was 100 g.

[0170] Table 3 Pure physical sunscreen product formula

[0171]

[0172]

[0173] Note: The raw materials in Table 3 are connected by “&”, which means that the component is a composite raw material, a whole, a commercially available product, and a conventional substance in this field.

[0174] 2. The pure physical sunscreen products of Application Example 1 and Application Comparative Example 1 are prepared by the following process steps:

[0175] (1) Weigh phase A into a beaker, heat to 80°C, and disperse evenly using high-speed homogenizer;

[0176] (2) Weigh the raw materials of phase B and add them into a beaker. Stir and dissolve evenly in a 70°C water bath.

[0177] (3) Slowly pour the mixture of step (2) into the mixture of step (1) under heating at 70° C. in a water bath and rapid stirring, stir evenly, and homogenize at high speed until emulsification is complete; start cooling, and when the temperature drops to below 40° C., add phase C and stir evenly at low speed;

[0178] (4) After the mixture is cooled to room temperature, the mixture is discharged to obtain a pure physical sunscreen product.

[0179] 3. Sun protection ability and water resistance test of pure physical sunscreen products

[0180] (1) The test method for sunscreen products in China's "Safety Technical Specifications for Cosmetics" (2015 edition) was used to test the SPF values ​​and PA grades of the pure physical sunscreen products of Application Example 1 and Application Comparative Example 1 to obtain their sunscreen capabilities. The results are shown in Table 4.

[0181] (2) The strong water resistance of the pure physical sunscreen products of Application Example 1 and Application Comparative Example 1 was tested using the method for determining the strong water resistance of sunscreen cosmetics in China's "Safety Technical Specifications for Cosmetics" (2015 edition). The results are shown in Table 4.

[0182] Table 4 Test results of sun protection ability and water resistance of pure physical sunscreen products

[0183]

[0184] (3) Microstructure observation test of pure physical sunscreen products:

[0185] Take a drop of pure physical sunscreen product on a glass slide, cover it with a glass slide, press it lightly, place it under a biological microscope, adjust the parameters of the 10x eyepiece and 10x objective lens, and observe the microscopic conditions of the material body of Application Example 1 and Application Comparative Example 1. See the attached for specific observations. Figure 3 .

[0186] From the results in Table 4 and the attached Figure 3 It can be seen that:

[0187] From the comparison results in Table 4, it can be seen that the SPF value and PA grade of Example 1 are higher than those of Comparative Example 1, that is, the modified nanopowder is applied to the sunscreen product with better sun protection ability and water resistance; the nanopowder is subjected to double organic polymer treatment to form a film-forming acrylic (ester) polymer and silicone resin on the surface, which directly improves the water and sweat resistance of the nanopowder itself, so that the nanopowder can quickly and self-controllably form a uniform and durable sunscreen film after application, and under the premise of keeping the content of the physical sunscreen unchanged, the uniform distribution of the sunscreen on the skin surface further improves the sun protection factor of the product.

[0188] From the attached Figure 3 It can be seen that compared with the application of comparative example 1, the material of the sunscreen product of application example 1 is more delicate, and no spontaneous agglomeration of the nanopowder due to its own small size effect and quantum size effect is observed. The monomer of acrylic (ester) polymer is used to carry out in-situ polymerization reaction and film coating on the surface of nanopowder, which improves the uniformity and density of the organic polymer coating layer and ensures the consistent performance of the nanopowder particles; further treatment with an outer layer of organic silicone resin further avoids the exposure of anions of acrylic (ester) polymer molecular chains and improves the compatibility and adaptability of nanopowder in the formula system; the surface of nanopowder is coated with a double-layer macromolecular organic polymer, so that the surface macromolecules of the nanopowder form steric hindrance when the nanopowder is used, and the single particles are dispersed in the system, thereby improving the stability of the product.

[0189] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A modified nano powder, characterized in that: The modified nano powder is a core-shell structure, with the nano powder as the core, and an inorganic hydrated oxide coating layer, an acrylic (ester) polymer coating layer and an organic silicone resin layer sequentially wrapped on the surface of the nano powder; The hydroxyl groups in the inorganic hydrated oxide coating layer are connected to the carboxyl groups in the acrylic acid (ester) polymer monomers through chemical bonding; In-situ polymerization of acrylic acid (ester) polymer monomers on the surface of the inorganic hydrated oxide coating layer forms an acrylic acid (ester) polymer coating layer; The hydroxyl group at the terminal group of the organic silicone resin is chemically bonded with the carboxyl group in the acrylic (ester) polymer to form the organic silicone resin layer.

2. The modified nano powder according to claim 1, characterized in that: The powder includes titanium dioxide and / or zinc oxide; The particle size of the nano powder is 10-100 nm.

3. The modified nano powder according to claim 1, characterized in that: The inorganic hydrated oxide coating layer includes aluminum hydroxide and / or silicon dioxide.

4. The modified nano powder according to claim 1, characterized in that: The acrylic polymer includes a polymer having an unsaturated group of acrylic acid.

5. A method for preparing a modified nanopowder as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Providing a slurry containing nano powder particles, and adjusting the slurry to be alkaline; Adding an inorganic coating agent to the alkaline slurry and mixing, then adding an acrylic acid (ester) polymer monomer and mixing and reacting to obtain powder A; Adding a silicone resin dispersion to the powder A and stirring evenly to obtain a powder B; The powder B is subjected to solid-liquid separation to obtain a solid phase, and the solid phase is the modified nanopowder.

6. The preparation method according to claim 5, characterized in that: The pH value of alkaline slurry is 9-10; The inorganic coating agent is selected from water-soluble aluminum salts and / or water-soluble silicon salts; The amount of the inorganic coating agent is 5-20wt% of the nano powder particles.

7. The preparation method according to claim 5, characterized in that: The amount of the acrylic acid (ester) polymer monomer is 1-15wt% of the nano powder particles; The monomers of the acrylic acid (ester) polymer include one or more of acrylic acid, methacrylic acid, octyl acrylic acid, ethylhexyl acrylate, methyl acrylate, lauryl methacrylate, ethyl acrylic acid, and propyl acrylic acid.

8. The preparation method according to claim 5, characterized in that: The silicone resin includes one or more of trimethylsiloxysilicate, polymethylsilsesquioxane, trimethylsiloxysilicate / polydimethylsiloxane crosspolymer, diphenylsiloxyphenyl polytrimethylsiloxane, polypropylsilsesquioxane, and polyphenylsilsesquioxane; The amount of the organic silicon resin used is 1-10 wt% of the nano powder particles.

9. A cosmetic, characterized in that: Including the modified nano powder according to claim 1.

10. The cosmetic according to claim 9, characterized in that: The cosmetics include sunscreen cream, liquid foundation, BB cream, CC cream, loose powder, primer or isolation cream.

Citation Information

Patent Citations

  • Composition based on multilayer spherical composite particles and on uv-screening agent

    CN107072893A

  • Water-proof anti-perspiration composition and sun-screening agent containing composition

    CN110339072A

  • Double-coat type make-up cosmetic product containing aluminum powder

    US5238678A